2015
DOI: 10.1007/s00284-015-0809-7
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Miniaturized Method for the Selection of Microbial Phenol Degraders Using Colourimetric Microtitration

Abstract: A high-throughput method is described, consisting of a colourimetric microtitration for screening phenol-degrading microorganisms, using a mixture of 4-aminoantipyrine and potassium ferricyanide as the colour indicator. This contemporary study summarizes a new method to determine phenol-degrading bacteria isolated from different areas. The method was used for testing a total of 72 bacteria collected from the natural environment and five known strains obtained from diagnostic and research laboratories employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…I-103 AB531392.1 (99% sequence identity), Bacillus thuringiensis KF150502.1 (100% sequence identity), and Bacillus cereus EU741099.1 (100% sequence identity) (Figure 1). Many authors reported about efficiency of Bacillus group for degradation of various toxic compounds [21][22][23][24].…”
Section: Bacillus Sp Cyr2mentioning
confidence: 99%
“…I-103 AB531392.1 (99% sequence identity), Bacillus thuringiensis KF150502.1 (100% sequence identity), and Bacillus cereus EU741099.1 (100% sequence identity) (Figure 1). Many authors reported about efficiency of Bacillus group for degradation of various toxic compounds [21][22][23][24].…”
Section: Bacillus Sp Cyr2mentioning
confidence: 99%
“…For molecular identification of decolorized isolates, Two universal primers supplied by Macrogen Company as a lyophilized form were used for isolation of specific 16S rRNA gene. 18 Lyophilized primers (27F with sequence 5'AGAGTTTGATCCTGGCTCAG-3'and 1492R with sequence 5'TACGGTTACCTTGTTACGACTT-3'sequences), both were dissolved in a nuclease free water to give a final concentration of 100 pmol/μL as a stock solution. A working solution of these primers was prepared by adding 10 μL of primer stock solution…”
Section: Primers Preparationmentioning
confidence: 99%
“…Toledo et al (2006) reported that strains Bacillus pumilus, and Bacillus subtilis were able to grow and utilize PAH compounds such as naphthalene, phenanthrene, fluoranthene and pyrene. Kuang et al (2013) reported 62% degradation of phenol at 200 mg/l concentration using Bacillus fusiformis within 7 h. Fayidh et al (2015) reported 43% and 94% degradation of phenol at 200 mg/l concentration using Bacillus sp. and Bacillus cereus, respectively.…”
Section: Poly-aromatic Compounds Degradationmentioning
confidence: 99%